(untitled) (Globalization and Business, 2023)
Financial Statement of the Organization for Financial Reporting Analysis The main objective of any economic process, including financial analysis, is the first: to identify the reasons for the financial stability of the organization and to set the measurements to eliminate them; Second, in case of maintaining existing tendencies of the enterprise, the prediction about the expected results; On the basis of modeling, find ways and means of ensuring financial sustainability. The article describes the FINSIM_PRO2018 simulator created by our financial statements.